Determination of Antimicrobial and Antioxidant Activity of Atropa belladonna L. - Sayım, Merve Ülkü; Pala, Rüveyde; Yaman, Cenker; Gül, Gizem; Benek, Atakan; Turu, Dilay; Bozyel, Mustafa Eray; Canlı, Kerem (Kastamonu University, 2025)
Aim of study: Bacteria that have developed resistance to antibiotics have become one of the major challenges facing global healthcare systems. This study evaluates the antimicrobial and antioxidant effects of Atropa belladonna extracts against an extended variety of microbial strains, addressing the urgent need due to increasing resistance. Material and method: In this study, disc diffusion, minimum inhibitory concentration testing, and DPPH antioxidant analyses were conducted on the Atropa belladonna plant. Main results: Using the ethanol extract, antimicrobial activity was tested against 26 bacterial and one yeast strain by disc diffusion, showing inhibitory effects on six microorganisms (four standard strains and two food isolates). MIC assays identified activity against Bacillus subtilis DSMZ 1971, Candida albicans DSMZ 1386, and Enterococcus durans. The DPPH assay demonstrated the greatest antioxidant activity at 200 mg/mL concentration, reaching 71.34%. Research highlights: The study results emphasize the need to consider Atropa belladonna’s antimicrobial and antioxidant capacities. Therefore, the study should be combined with various doses, strains, or methods.